2018
DOI: 10.2217/fon-2017-0540
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SlC7A11: A Novel Oncogene and an Indicator of Unfavorable Prognosis for Liver Carcinoma

Abstract: SLC7A11 overexpression might be a novel biomarker and a potential unfavorable prognostic factor as well as a potential therapeutic target for liver carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…e results of our GO and KEGG analyses also suggested that the 6 mRNAs were mainly enriched in cell cycle pathways, including the cell cycle, regulation of the cell cycle, and cell cycle processes. CEP55, EZH2, and SLCA11 are highly expressed in HCC and play critical regulatory roles in cancers [21][22][23]. ey were key nodes that made up the stage I HCC ceRNA network in our study and were key potential prognostic genes in stage I HCC, results that are consistent with a Gene Expression Omnibus (GEO) database study by Yue et al [24].…”
Section: Discussionsupporting
confidence: 89%
“…e results of our GO and KEGG analyses also suggested that the 6 mRNAs were mainly enriched in cell cycle pathways, including the cell cycle, regulation of the cell cycle, and cell cycle processes. CEP55, EZH2, and SLCA11 are highly expressed in HCC and play critical regulatory roles in cancers [21][22][23]. ey were key nodes that made up the stage I HCC ceRNA network in our study and were key potential prognostic genes in stage I HCC, results that are consistent with a Gene Expression Omnibus (GEO) database study by Yue et al [24].…”
Section: Discussionsupporting
confidence: 89%
“…We conducted qRT-PCR experiments on 20 pairs of HCC-and adjacent liver-tissue samples, and the result showed that expression levels of the 13 key potential prognostic genes were consistent with the result of our previous analysis. Among these key potential prognostic genes, CCNB1 ,20 CEP55 ,21 CHEK1 ,22 EZH2 ,23 KPNA2 ,24 LRRC1 ,25 PBK ,26 RRM2 ,27 SLC7A11 ,28 and ZWINT 29 have been validated as oncogenes in HCC according to previous studies. Interestingly, no studies have reported a relationship between SUCO gene expression and tumorigenesis, and we are planning to conduct experiments to explore the role of SUCO in the development and progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…SLC7A11 is the functional light chain subunit of the cystine/glutamate antiporter system x c and confers specificity for cystine uptake, a major rate-limiting factor in glutathione biosynthesis (19). SLC7A11 is overexpressed in several cancer types, including glioma, liver carcinoma, non-small cell lung cancer, and triple-negative breast cancer, and serves as an independent prognostic factor (20)(21)(22)(23)(24). SLC7A11 also contributes to glutathione-based drug resistance (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%